PENGARUH PERASAN MENGKUDU TERHADAP PERTUMBUHAN BAKTERI STAPHYLOCOCCUS AUREUS - Irmanita Wiradona; Suwarsono Suwarsono; Lanny Sunarjo; Hermien Rimbyastuti (Jurnal Kesehatan Gigi, 2015)
TITLEThe effect of mengkudu squeeze toward growth of Staphylococcus aureusABSTRACT Staphylococcus aureus is a bacterium causes of dental and oral diseases, especially periodontal disease. Efforts to prevent one of them with natural ingredients that Noni. Noni (Morinda citrifolia Linn) contains anthraquinone is used as an antibacterial. The purpose of this study was to determine the effect of concentration of noni (Morinda citrifolia Linn) on the inhibition of the growth of Staphylococcus aureus bacteria.This is  a quasi-experimental study. Research subjects bacterium Staphylococcus aureus. The study was conducted using a concentration of 40%, 60% and 80% respectively – each concentration done 3x treatment. The data was analyzed with deskriptif kuantitatif.The results showed a large area of inhibition of the average noni solution with a 40% concentration of 9.34, a 60% concentration of 9.74, and the concentration of 80% by 10.74 mm.  The conclusion of this study is the average total diameter of inhibitation, most notably at a concentration of 80%. Keywords: Noni Juice, Staphylococcus aureus